Nest defense behavior against ant attacks in post-emergent colonies of wasp Mischocyttarus cerberus (Hymenoptera, Vespidae) - Togni, Olga Coutinho [UNESP]; Giannotti, Edilberto [UNESP] (Springer Heidelberg, 2008)
The primitive eusocial wasp Mischocyttarus cerberus forms colonies of independent foundation, without morphological differentiation among castes. Ants are natural enemies of the social wasps and defending the wasps' nests involves chemical and active defense strategies. The aims of this work were to verify the kind of defense the wasps use most frequently in post-emergent colonies of M. cerberus. We also observed whether the nest was abandoned during the ant attack and whether any relationship existed between the forms that colony defense took and the number of adults, the number of cells, and the number of immature wasps. The study was carried out on the campus of Universidade Estadual Paulista of Rio Claro, São Paulo, Brazil. The 23 nests under study were mapped weekly, and 68 bioassays were performed by simulating ant attacks against the nests. The results showed that wasps used both active and chemical strategies for nest defense, and the PCA analysis showed that the aggressive behaviors of biting the ant, wings vibrating, gaster hitting, and abdomen pumping were the dominant terms; the PCA correlation values were 2.70, 2.54, 1.64, and 1.63, respectively. The colonies in pre- and post-male substages with few immature wasps and the nests in post-male substage with one adult were more correlated with the nonaggressive behaviors of hiding, staying immobile, and flying; their PCA correlation values were 3.12, 2.56, and 1.77, respectively. These results show that the number of immature wasps is an important factor in the kind and in the intensity of the defense behavior against ant attacks.
Keywords: nest defense; Mischocyttarus; Camponotus; post-emergence